Integrasi Pendidikan Karakter di Kurikulum Pendidikan Guru Madrasah Ibtidaiyah - Fatima zahra, Siti; Aminah, Siti (ELEMENTARY : Journal of Primary Education, 2024)
This research explores the integration of character education in the teacher education curriculum at Madrasah Ibtidaiyah and its impact on the quality of education at the institution. Character education, which includes the formation of moral and social values, is a crucial component in the education process in Madrasah Ibtidaiyah, an institution that combines aspects of general science with religious teachings. This article uses the literature review method to analyze recent studies, policies and best practices related to the implementation of character education in the teacher education curriculum. The findings of this study show that the integration of character education in the curriculum not only enriches teachers' pedagogical competencies but also strengthens their ability to shape students' positive character. Well-integrated character education allows teachers to develop holistic teaching methods, covering academic, moral and social aspects. However, effective implementation still faces various challenges, including a lack of adequate training, limited resources and inconsistent institutional support. This article recommends the need for increased specific training on character education for prospective teachers as well as strengthened support from educational institutions to ensure that character education can be effectively integrated in the curriculum. Thus, successful integration is expected to have a significant positive impact on the quality of education in Madrasah Ibtidaiyah and contribute to the formation of a young generation that is not only academically intelligent but also virtuous.